2016
DOI: 10.1039/c6an00248j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic impurities in single-walled carbon nanotubes and graphene: a review

Abstract: Control over magnetism in single-walled carbon nanotubes (SWCNTs) and graphene is of fundamental importance. Creation and manipulation using the unpaired spins without the need for archetypal magnetic elements results in sp(2)-hybridised nanocarbons being at the forefront of applications in both spintronics and nanoelectronics. The crucial limitation for the experimental observation of the intrinsic carbon magnetism stems from the presence of magnetic impurities, from which a magnetic response usually dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 166 publications
(240 reference statements)
1
25
0
Order By: Relevance
“…The most significant issue of LPE processing, however, is that the necessary shear/oxidation introduces defects into the carbon framework and diminishes their aspect ratio 112 ( Figure 7). As a result, the intrinsic electronic, 113 magnetic, 114 and mechanical 37 properties of LPE-derived graphene and LPE-processed SWCNTs are diminished compared to CVD-grown/mechanically exfoliated graphene, and as-grown SWCNTs, respectively. 83,108,109 The processing of fullerenes is generally less challenging than that of graphene and nanotubes due to their solubility in a range of solvents, commonly toluene and carbon disulfide, 115 and higher concentrations may be accessed using either specialist solvents (e.g., 1-halo-naphthalenes 116 ) or fullerene functionalization.…”
Section: Electronic Properties Of Neutral Carbon Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant issue of LPE processing, however, is that the necessary shear/oxidation introduces defects into the carbon framework and diminishes their aspect ratio 112 ( Figure 7). As a result, the intrinsic electronic, 113 magnetic, 114 and mechanical 37 properties of LPE-derived graphene and LPE-processed SWCNTs are diminished compared to CVD-grown/mechanically exfoliated graphene, and as-grown SWCNTs, respectively. 83,108,109 The processing of fullerenes is generally less challenging than that of graphene and nanotubes due to their solubility in a range of solvents, commonly toluene and carbon disulfide, 115 and higher concentrations may be accessed using either specialist solvents (e.g., 1-halo-naphthalenes 116 ) or fullerene functionalization.…”
Section: Electronic Properties Of Neutral Carbon Nanomaterialsmentioning
confidence: 99%
“…can constitute impurities, if not the desired structure; for example, (multiwall-)fullerenes are often found in arc-grown CNT samples, or MWCNTs may contaminate SWCNT samples. Inorganic impurities, in the form of residual metal catalyst particles (often in graphitic shells) or residual catalyst substrates, can increase material density and are capable of altering the electronic, 144 magnetic, 114 and physical properties of the nanocarbon. In general, impurities complicate stoichiometric control of nanocarbon charging, as the charge segregation between nanomaterial and impurities is not yet well-understood.…”
Section: Starting Materialsmentioning
confidence: 99%
“…Previous studies showed that CNTs produced by different methods (including chemical vapour deposition and laser ablation) contain metal impurities, mainly Fe, Ni and Co, inside the tubes, which are covered with layers of graphene sheets [19, 20]. Today, most studies reporting preparation of MCNTs ( S1 Table ), seem to have overlooked three important facts.…”
Section: Introductionmentioning
confidence: 99%
“…Today, most studies reporting preparation of MCNTs ( S1 Table ), seem to have overlooked three important facts. First, commercial CNTs with metallic impurities can be inherently magnetic due to the presence of Fe, Ni and Co in their metallic form [19, 21, 22]. Second, metallic impurities are hard to remove, even with concentrated acids at high temperature [2325].…”
Section: Introductionmentioning
confidence: 99%
“…Although ICP is rather common, the analyzed amount of magnetic impurities is typically underestimated as not the sample but the components soluble in the standardized nitric acid are detected. 33 To further explore the origin of magnetism, we conducted EPR measurement. From the EPR spectra (Fig.…”
mentioning
confidence: 99%